A Rice NAC Transcription Factor Promotes Leaf Senescence via ABA Biosynthesis . Issue 3 (12th May 2017) - Mao, Chanjuan; Lu, Songchong; Lv, Bo; Zhang, Bin; Shen, Jiabin; He, Jianmei; Luo, Liqiong; Xi, Dandan; Chen, Xu; Ming, Feng
Abstract : The NAC transcription factor OsNAC2 plays an important role in ABA-dependent leaf senescence by targeting both abscisic acid biosynthetic and senescence-associated genes. Abstract: It is well known that abscisic acid (ABA)-induced leaf senescence and premature leaf senescence negatively affect the yield of rice ( Oryza sativa ). However, the molecular mechanism underlying this relationship, especially the upstream transcriptional network that modulates ABA level during leaf senescence, remains largely unknown. Here, we demonstrate a rice NAC transcription factor, OsNAC2, that participates in ABA-induced leaf senescence. Overexpression of OsNAC2 dramatically accelerated leaf senescence, whereas its knockdown lines showed a delay in leaf senescence. Chromatin immunoprecipitation-quantitative PCR, dual-luciferase, and yeast one-hybrid assays demonstrated that OsNAC2 directly activates expression of chlorophyll degradation genes, OsSGR and OsNYC3 . Moreover, ectopic expression of OsNAC2 leads to an increase in ABA levels via directly up-regulating expression of ABA biosynthetic genes ( OsNCED3 and OsZEP1 ) as well as down-regulating the ABA catabolic gene ( OsABA8ox1 ). Interestingly, OsNAC2 is upregulated by a lower level of ABA but downregulated by a higher level of ABA, indicating a feedback repression of OsNAC2 by ABA. Additionally, reduced OsNAC2 expression leads to about 10% increase in the grain yield of RNAi lines. The novel ABA-NAC-SAGs regulatory module might provide a new insight into the molecular action of ABA to enhance leaf senescence and elucidates the transcriptional network of ABA production during leaf senescence in rice.